A Mystery Tale: Nickel Is Fickle When Snails Fail—Investigating the Variability in Ni Toxicity to the Great Pond Snail. (31st August 2020) - Crémazy, Anne; Brix, Kevin V; Smith, D Scott; Chen, Weibin; Grosell, Martin; Schlekat, Christian E; Garman, Emily R; Middleton, Elizabeth T; Wood, Chris M
ABSTRACT: Dissolved Ni concentrations inhibiting the growth of juvenile great pond snails ( Lymnaea stagnalis ) have been documented to vary from about 1 to 200 µg L −1 Ni. This variability makes L. stagnalis either a moderately sensitive or the most sensitive freshwater species to chronic Ni exposure tested to date. Given the role of sensitive species in environmental risk assessment frameworks, it is particularly important to understand this variability, i.e., to characterize the factors that modulate Ni toxicity and that may confound toxicity test outcomes when uncontrolled. In the present study, we tested if this variability was due to analytical (growth calculation: biomass versus growth rate), environmental (water quality), lab‐specific practices, and/or snail population differences among earlier studies. Specifically, we reanalyzed previously published Ni toxicity data and conducted additional measurements of Ni aqueous speciation, short‐term Ni uptake, and chronic Ni toxicity with test waters and snail cultures used in previous studies. Corrections for Ni bioavailability and growth calculations explained a large degree of variability in the published literature. However, a residual 16‐fold difference remained puzzling between 2 studies: Niyogi et al. (2014) (low ECxs) and Crémazy et al. (2018) (high ECxs). Indeed, differences in metal bioavailability due to water chemistry, lab‐specific practices, and snail population sensitivity could not explain the large variation in Ni toxicity in these 2 very similar studies. Other potentially important toxicity‐modifying factors were not directly evaluated in the present work: test duration, diet, snail holding conditions, and snail age at onset of testing. The present analysis highlights the need for further studies to elucidate 1) the mechanisms of growth inhibition in Ni‐exposed L. stagnalis and 2) the important abiotic and biotic factors affecting this biological response. Until these processes are understood, substantial uncertainties will remain about inclusion of this species in Ni environmental risk assessment. Integr Environ Assess Manag 2020;16:983–997. © 2020 SETAC KEY POINTS: Nickel concentrations inhibiting the growth of Lymnaea stagnalis vary by 2 orders of magnitude (1–200 µg L −1 ) in the literature. The interstudy variability on EC20s was decreased by using specific growth rate instead of biomass as the response variable (by a factor of 5‐fold) and by bioavailability correction with the BLM (by a factor of 3‐fold). A remaining 7‐fold variation in reported EC20s could not be explained by differences in test waters, snail populations, and lab‐specific practices. Other potentially important toxicity‐modifying factors remain to be studied (e.g., test duration and snail age and diet).